The Impact of Customer Satisfaction on Repurchase Intention (Surveys on Customer of Bloomythings) - Nurul Tufahati; Cecep Safa'atul Barkah; Pratami Wulan Tresna; Arianis Chan (Universitas Bunda Mulia, 2021)
This study seeks to determine whether customer satisfaction influences repurchase intentions from Bloomythings' customers and to implement strategies to increase consumer satisfaction and repurchase intention of Bloomythings. The resources obtained are then analyzed using quantitative research methods by conducting validity and reliability tests, normality tests, heteroscedasticity tests, and simple linear regression analysis to determine the effect of customer satisfaction on repurchase intention. This kind of survey is a survey supported by the distribution of questionnaires as a data collection tool. The samples in this study are customers from Bloomything who have made purchases on Bloomythings products. The results showed that customer satisfaction had a positive and significant impact on repurchase intention.